2010
DOI: 10.1158/0008-5472.can-09-2408
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Viral Therapy for Prostate Cancer: Efficacy of Reovirus as a Biological Therapeutic

Abstract: Reovirus is a nonattenuated double-stranded RNA virus that exploits aberrant signaling pathways allowing selective cytotoxicity against multiple cancer histologies. The use of reovirus as a potential treatment modality for prostate cancer has not previously been described, and in this study evidence of in vitro and in vivo activity against prostate cancer was seen both in preclinical models and in six patients. The human prostate carcinoma cell lines PC-3, LN-CaP, and DU-145 exposed to replication-competent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 37 publications
5
79
0
1
Order By: Relevance
“…6 By comparison, targeted virotherapy has the potential to selectively kill cancer cells while sparing normal cells. 8,24 In this regard, our laboratory has previously demonstrated that eIF4E is a good discriminatory factor between normal and cancer cells as eIF4E levels are substantially elevated in the latter. 4,15,20 eIF4E is the rate-limiting subunit of the eIF4F complex, which is comprised of eIF4E, the cap binding protein; eIF4A, an ATPase and RNA helicase; and eIF4G, a scaffolding protein.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 By comparison, targeted virotherapy has the potential to selectively kill cancer cells while sparing normal cells. 8,24 In this regard, our laboratory has previously demonstrated that eIF4E is a good discriminatory factor between normal and cancer cells as eIF4E levels are substantially elevated in the latter. 4,15,20 eIF4E is the rate-limiting subunit of the eIF4F complex, which is comprised of eIF4E, the cap binding protein; eIF4A, an ATPase and RNA helicase; and eIF4G, a scaffolding protein.…”
Section: Discussionmentioning
confidence: 98%
“…7 In addition, there is clinical evidence that viruses can be used to safely control treatment-resistant prostate cancer. 8 Viruses such as vesicular stomatitis virus often demonstrate a preference to infect and replicate in tumor cells owing to the presence of a faulty interferon response. 7,9 These studies demonstrate the potential use of viruses as an option for targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the clinical trials, six are in partnership with the US National Cancer Institute, and four are in partnership with the National Cancer Institute of Canada Clinical Trials Group. So far, 308 patients have been treated with reovirus in completed studies; approximately 610 patients are currently enrolled in ongoing trials, and it is expected that an additional 631 patients will be enrolled in future trials.Reovirus has been or will be used in 12 ) has been tested in various clinical trials for the treatment of a multitude of cancers, such as prostate cancer, [48][49][50] malignant gliomas, [51][52][53] advanced head and neck cancers, [54][55][56][57] and metastatic ovarian cancers, [58][59][60] among others…”
Section: Clinical Studies With Reovirusmentioning
confidence: 99%
“…Based on the safety data from this first trial, a translational study was designed to assess the oncolytic activity (ie, the efficacy) of reovirus in preclinical models and in six prostate cancer patients. [48] In this study, the prostate cancer patients first received a single reovirus injection of 1×10 7 plaque-forming units, and 3 weeks later underwent prostatectomies. Importantly, the immunohistochemical analysis of resected prostate tissues from these patients revealed a preference of reovirus to infect cancerous tissue rather than noncancerous tissue.…”
Section: Monotherapymentioning
confidence: 99%
“…As a monotherapy, revorius administration generates antitumor responses across a broad range of tumor histologies. Tumor regression has been observed in colorectal and ovarian cancer models (36), xenograft breast cancer models and against primary breast tumor samples (37), prostate xenograft models and six organ-confined prostate cancer patients (38), hamster models of liver metastases from pancreatic cancer (39), and glioblastoma stem-like cells (40). Although the initial monotherapeutic results may indicate some therapeutic activity, OVs as standalone therapies have rarely been shown to induce complete, durable regressions of established tumors in vivo (41).…”
Section: Mechanism Of Tumor Lysismentioning
confidence: 99%